Using Rummy Game Method to Improve Students’ Learning Activities and English Dialog - Supriyanto Supriyanto (IAIN Salatiga, 2012)
This classroom action research was aimed at improving students’ learning activities and students’ English dialog skills in the state senior high school 3 Salatiga. The research was carried out in the state senior high school 3 Salatiga from January to June 2012. The subject of the research was 38 students of grade XI natural science 2. While the objects of research were rummy game method, students’ learning activities and students’ English dialog skills. This action research was conducted in two cycles. Each consisted of planning, acting, observing, and reflecting. In cycle 1, the researcher implemented rummy game method with big groups and ready made cards while in cycle 2, the researcher applied rummy game method with small groups and student designed cards. To collect the data the researcher gave self-assessment test and performance test before the first cycle, after the first cycle, and after the second cycle. The data analysis was done by descriptive comparison namely by comparing scores in the previous condition with those of the first cycle and the second cycle. The research findings revealed that there was significant improvement of average scores in students’ learning activities namely 13.8 % from 56.8 % in the previous condition to 70.6 % in cycle 2 and in students’ English dialog skill namely 5.8 from 72.7 in the previous condition to 78.5 in cycle 2. Hence, hypothesis stating that using rummy game method is able to improve students’ learning activities and English dialog skill in the state senior high school 3 Salatiga grade XI natural science 2 even semester year 2011/2012 is proven right.Keywords: Rummy Game Method; Learning Activities; English Dialog Skill